IN UZBEKISTAN, RELIGIOUS AND EDUCATIONAL REFORMS BASED ON THE LESSONS OF HISTORICAL MEMORY ARE TAKING PLACE ON A LARGE SCALE - Yusupov Rasuljon Malikovich (Modern American Journals, 2025)
This article examines the historical foundations and contemporary significance of religious and educational reforms in Uzbekistan, drawing on the lessons of historical memory. It highlights the views of Sheikh Hasan ibn Abdullah, who emphasized studying history as a bridge between past and present generations. The article analyzes the Soviet regime’s restrictive policy toward Islam, including the persecution of religious scholars, closure of religious institutions, and strict control over religious practices. Special attention is given to the establishment of the Religious Administration of Muslims of Central Asia and Kazakhstan in 1943, the roles of its key figures Eshon Babakhan Abdulmajidkhan and Ismail Makhdum Sattiev and the mechanisms of religious supervision during the Soviet era. The study further explores the significant reforms carried out in independent Uzbekistan, including the restoration and construction of mosques, institutional improvements, and the expansion of religious and educational opportunities. These reforms underscore Uzbekistan’s efforts to revive national and religious values, strengthen spiritual heritage, and promote a harmonious and enlightened society.
Keywords: Historical memory, Islam in Uzbekistan, Soviet religious policy, Religious Administration of Muslims of Central Asia and Kazakhstan, Sheikh Hasan ibn Abdullah, Eshon Babakhan Abdulmajidkhan, Ismail Makhdum Sattiev, religious reforms, independence of Uzbekistan, mosques, religious organizations, spiritual heritage.